Learning Ecosystem using New Normal Active Administrative Innovation in Thai Society - et. al., PhraWisutthiphongmethee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: Learning ecosystem has been using in educational context in different areas to enhance the development of leaning ability in current situation. The purpose of this article was to propose learning ecosystem using new normal active administrative innovation in Thai society. Documentary study and qualitative research synthesis were used for the study. Results showed that 1) there are four aspects to consider of setting learning ecosystem that consisted of learning differently, supportive collaborative learning, self-directed learning, and thinking utilization. 2) New normal active administrative innovation is an active administration applying constructivism concept that consisted of knowledge, persuasion, decision, implementation, and confirmation. The nature of innovation should have relative advantage, compatibility, less complexity, divisibility, and visibility. 3) e-Learning Ecosystem will be applied in new normal active administrative innovation with 3 aspects consisted of (1) content providers offer content for learning solutions that is linked to competency development and personal development, (2) consultants which are strategy consultant, compensation consultant, information technology consultants, and implementation consultants, and (3) Infrastructure which are learning content management system, content delivery system and tools. Learning ecosystem is not started from how teacher design the lesson, but it will start from acceptance the difference of learners, teachers, parents, and community by performing roles of giving and taking knowledge from learners on supportive collaborative learning